Employees with Communication as an Intervening Variable at Bank Indonesia Representative Office in North Sumatra Province - Intan Lydia Tarida Mahdalena; Kiki Farida Ferine (International Journal of Management, Economic and Accounting, 2024)
In this case, HR is clearly not a major asset but rather a well-defined and expandable asset, compared to an investment portfolio, and also not the other way around as a liability. From this point of view, HR is an investment in a more mature institution or organization. The results of this study are as follows: Communication has a positive and significant effect on Employee Performance with the original sample value of 0.493 and p values of 0.000. Work Quality had a positive and significant effect on Employee Performance with the original sample value of 0.370 and p values of 0.008. Work Quality has a positive and significant effect on Communication with an original sample value of 0.779 and p values of 0.000.Work Stress has a negative and insignificant effect on employee performance with an original sample value of -0.026 and p values of 0.398 Work Stress has a positive and significant effect on communication with an original sample value of -0.176 and p values of 0.016 Work Quality has a positive and significant effect on Employee Performance through Communication with an original sample value of 0.385 and p values 0.001.